Targeting Long Non-Coding RNAs in Nervous System Cancers: New Insights in Prognosis, Diagnosis and Therapy - Malissovas, Nikos; Ninou, Elpinickie; Michail, Artemis; Politis, Panagiotis K. (Current Medicinal Chemistry, 2019)
Long non-coding RNAs (lncRNAs) constitute one of the most broad and diverse classes of cellular transcripts, playing key roles as regulatory molecules in many biological processes. Although the biology of lncRNAs is a new and emerging field of research, several studies have already shown that alterations in the expression of lncRNAs are associated with the development and progression of cancer in different organs and tissues, including central and peripheral nervous system. In this review, we summarize the oncogenic and tumor suppressive roles of lncRNAs in malignant tumors of the nervous system, such as glioma and neuroblastoma, focusing on their functional interactions with DNA, other RNA and protein molecules. We further discuss the potential use of lncRNAs as biomarkers for diagnosis, prognosis and tumor treatment. Gaining insight into the functional association between nervous system malignancies and lncRNAs could offer new perspectives to the development of promising therapeutic tools against cancer.
Keywords: Glioblastoma